Standardization of Software Functional Size Measurement Methods - Czarnacka-Chrobot, Beata (Advanced Information Technologies for Management – AITM 2009, 2009)
Execution of application software development and enhancement projects encounters many problems, which may be proved by its unsatisfactory effectiveness, leading to considerable financial losses. One of the key reasons behind this status quo is lack of clear-cut measure for such projects product size, which may be regarded as one of the fundamental problems of software engineering. As a result of many years' verification of various approaches to software size measurement reliability and objectivity, this is only the concept called software Functional Size Measurement (FSM) that so far has been standardized by ISO and I EC. Set of rules for such measurement was included in the 6-part norm ISO/IEC 14143. Being compliant with this norm, five of the FSM methods have also been standardized by these organizations. In this paper the author attempts to make synthetic comparison of two most popular normalized FSM methods, dedicated especially for business software systems, namely IFPUG and COSMIC methods.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 85, s. 40-50